Impact of early percutaneous dilatative tracheostomy in patients with subarachnoid hemorrhage on main cerebral, hemodynamic, and respiratory variables: A prospective observational study - Bini, Giovanni; Russo, Emanuele; Antonini, Marta Velia; Pirini, Erika; Brunelli, Valentina; Zumbo, Fabrizio; Pronti, Giorgia; Rasi, Alice; Agnoletti, Vanni (Frontiers in Neurology, 2023)
Background: Patients with poor grade subarachnoid hemorrhage (SAH) admitted to the intensive care unit (ICU) often require prolonged invasive mechanical ventilation due to time to obtain neurological recovery. Impairment of consciousness and airway protective mechanisms usually require tracheostomy during the ICU stay to facilitate weaning from sedation, promote neurological assessment, and reduce mechanical ventilation (MV) duration and associated complications. Percutaneous dilatational tracheostomy (PDT) is the technique of choice for performing a tracheostomy. However, it could be associated with particular risks in neurocritical care patients, potentially increasing the risk of secondary brain damage. Methods: We conducted a single-center, prospective, observational study aimed to assess PDT-associated variations in main cerebral, hemodynamic, respiratory variables, the occurrence of tracheostomy-related complications, and their relationship with outcomes in adults with SAH admitted to the ICU of a neurosurgery/neurocritical care hub center after aneurysm control through clipping or coiling and undergoing early PDT. Results: 50 patients were included. PDT was performed after a median of 4 days (IQR 3; mean 4.3, SD ± 2.1) after ICU admission. We observed a temporary increase in ICP during early PDT; this increase was statistically significant in patients presenting with higher Therapy Intensity Level (TIL) at the time of the procedure. An episode of ICP > 20 mmHg occurred in more than one half of patients; in 20 of them interventions aimed at lowering ICP were implemented. No significant relationship was observed between periprocedural intracranial hypertension and outcome measures. Considering the entire population, periprocedural CPP variation was not significant. PaCO2 appeared stable among the whole group. We observed periprocedural PaO2 consistently above 150 mmHg, even if this parameter varied significantly during the procedure.The 6 months outcome, according to the GOS, was not significantly different between patients in the H-ICP and N-ICP groups. Conclusions: The episodes of intracranial hypertension we observed were brief, and appeared mainly due to the activation of cerebral autoregulatory mechanisms in patients with impaired compensatory mechanisms and compliance. The low number of observed complications might be related to our organizational strategy, all based on a dedicated "tracheo-team" implementing both PDT following a strictly defined protocol and accurate follow-up.